A SCENARIO-BASED HYDROLOGICAL SIMULATION FRAMEWORK FOR CLIMATE-RESILIENT IRRIGATION WATER ALLOCATION IN TROPICAL WATERSHEDS - Abd Rakhim Nanda (Nusantara Hasana Journal, 2025)
Rainfall variability and climate uncertainty increasingly affect irrigation water availability in tropical watersheds. This study develops a scenario-based hydrological simulation framework for climate-resilient irrigation water allocation. The framework integrates rainfall scenario development, runoff estimation, evapotranspiration-based crop water requirement, water availability assessment, and monthly water balance analysis. Five rainfall scenarios were simulated, consisting of normal rainfall, moderate rainfall deficit, severe drought, extreme drought, and extreme rainfall conditions. The results show that reduced rainfall substantially decreases water availability and increases irrigation deficit during the dry season. Irrigation reliability declined from 75% under normal conditions to 60%, 42%, and 25% under moderate, severe, and extreme drought scenarios, respectively. In contrast, the extreme rainfall scenario increased reliability to 85%, although it may intensify runoff and flood risk. The proposed framework supports adaptive irrigation scheduling, crop calendar adjustment, storage optimization, and climate-resilient water allocation planning.